Supply Chain Management in the Catfish Seed Market - Emmy Lilimantik; Wildan Rafi (International Journal of Supply Chain Management, 2019)
This study examines the Supply Chain Management (SCM) of the catfish seed market in the Mustafa K Company in the South Kalimantan Province in Indonesia. Cultivation of catfish cannot be separated from seed availability arrangement. Excess inventory can lead to an increase in storage costs, while a shortage of inventory causes farmers to not carry out cultivation. Supply chain management can be applied to help plan and control seed stock at optimum level so that efficient management and delivery of seeds. This study uses primary and secondary data and the qualitative method to examine SCM coverage area and the Snowball Sampling method to examine the supply chain model. The results show that the company obtains seeds from a different source to ensure quality. The maintenance criteria for fish seeds consist of three sizes of 1, 1.5, and 2 inches to minimize mortality rate and focus on quality level before selling it to fish farmers. The distribution system considers the minimum quantity of seed orders, delivery distance, and time of delivery. The companys Supply Chain Model involves suppliers (Company Agent of Zahra Catfish seeds), Distributors (Individual Company Mustafa K), and Customers (fish farmers). Implementing SCM in the fishery sector will improve the quality and quantity of fishery products.